PENERAPAN MODEL PEMBELAJARAN GIVING QUESTION AND GETTING ANSWER UNTUK MENINGKATKAN KINERJA GURU DALAM MENGAJAR DI SMPN 4 MINAS - Nurhasni Nurhasni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
School action research (PTS) is a research report based on the experience of the authors in applying learningmodel giving question and getting answer in an effort to improve teacher performance in teaching at SMPN 4Minas. The goal is to find out whether teacher performance in teaching can be improved through the model ofgiving questions and getting answer in SMPN 4 Minas. The sample taken in this action research is 30 people,that is teacher from SMPN 4 Minas. The research procedure in this research is divided into two cycles, eachcycle consists of four main activities, namely planning, implementation, observation and reflection. Datacollection techniques in this study using observation. From the description of data processing and discussion itcan be concluded that the performance of teachers is obtained in the first cycle of 60.7% with good category andin the second cycle increased to 84.50% with good category. This means that the model of learning givingquestion and getting answer can improve teacher performance in teaching in SMPN 4 Minas said successful